2011
DOI: 10.1590/s0100-69912011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma gástrico Borrmann tipo IV: análise dos resultados da ressecção curativa

Abstract: Results Results Results Results: Of the 123 patients studied, 68 underwent gastrectomy, 52 (42.3%) with curative intent and 16 (13%) palliative resection, while 55 (44.7%) had disease not subject to resection. Three postoperative deaths followed the curative resection, constituting a mortality rate of 5.76%. In nine (17.3%) patients there were technical complications, and esophagojejunal fistula seven cases, the most frequent. All technical complications and deaths occurred after total gastrectomy, which was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…5a ). Six studies reported median survival times for B-4 patients after non-curative resection or non-resection [ 13 , 14 , 20 – 23 ]. In these studies, 434 patients underwent non-curative resection and 304 patients underwent non-resections, such as an exploratory laparotomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a ). Six studies reported median survival times for B-4 patients after non-curative resection or non-resection [ 13 , 14 , 20 – 23 ]. In these studies, 434 patients underwent non-curative resection and 304 patients underwent non-resections, such as an exploratory laparotomy.…”
Section: Resultsmentioning
confidence: 99%
“…At present, most physicians do not recommend LUAE + Apl because it is not effective for patients with stage IV gastric cancer and may cause severe post-operative complications. Besides, some researchers believe that extended lymphadenectomy should be performed if patient’s clinical condition allowed, because it may allow a better assessment of nodal stations and decrease the chance of stage worsening [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric carcinoma is a fairly prevalent malignancy worldwide, representing the second leading cause of death secondary to cancers [1]. Despite recent medical advances, the outcome secondary to gastric cancer remains discouragingly and the survival rate of advanced disease stages is decreased.…”
Section: Introductionmentioning
confidence: 99%